Socio economic factors influencing adoption of best management practices among cattle farming farmers in East Coast Economic Region (ECER) Malaysia. - Amal Najim Hasan. (2017)
Smallholder cattle farmers in ECER, Malaysia have problems in livestock production in terms of adopting best management practices (BMPs) in cattle farming, which demands attention from researchers and policy makers. Their adoption of BMPs was hypothesized to have been influenced by their socio-economic profile. This study investigates the issue. A sample of 608 cattle farmers in ECER covering Kelantan, Pahang, Terengganu and part of Johor was selected randomly and interviewed based on a questionnaire. It contained questions pertaining to 30 best cattle management practices covering feeding, breeding and healthcare. The socio-economic profile of the farmers such as education level, farmer‟s annual income, cattle farming as main occupation, type of owned cattle, sharing of training course, current knowledge, intention to training course, etc. were also recorded. The level of adoption of BMPs was measured on a scale of 1 to 30. The correlation and regression between farmers‟ adoption of BMPS and their socio-economic profiles were also studied. Results indicated that 50.5% of farmers are over 50 years, 57.2% of farmers have primary school education, 50.7% of them have an annual income < RM ‎10,000. The adoption level of BMPs among the sampled farmers was low (score = 9.27). On an average, 58% of the farmers had low level of adoption, 41% had medium level of adoption and only 1.0% of them had high level of adoption. Cattle farmers in Pahang had the highest level of adoption (score = 10.5) while those in Terengganu had the lowest level (score = 8.38). From the comparison of different functional forms, i.e. log-log, log-linear, linear-log, and linear-linear, the linear regression model is the best fit as it produced higher R2 value (0.223) and F- value (12.172). The socio-economic factors of farmers e.g. education level, farmer‟s annual income, cattle farming as main occupation, etc., were found to be significantly associated with adoption of BMPs, while farm size had a negative relationship with BMPs. The farmers adopted BMPs more in feeding than in breeding and healthcare. Different sets of socio-economic factors have influenced the level of adoption of BMPs in different states of ECER. Programs for increasing the adoption of BMPS in cattle farming in ECER were then proposed through provision of strategic training to smallholder farmers.